The Conformation and Assignment of the Proton NMR Spectrum in Water of DX600, a Bioactive Peptide with a Random Coil Conformation. (28th February 2011) - Steinmetz, Wayne E.; Carrell, Timothy N.; Peprah, Richard B.
Abstract : DX600, a small peptide with 26 residues, is a potent, highly selective inhibitor of angiotensin converting enzyme 2 (ACE2). A range of NMR methods including TOCSY and ROESY yield an assignment of its proton spectrum in water and constraints on its conformation. Constrained molecular dynamics simulations of solvated DX600 show that the peptide's most abundant conformer adopts a predominantly random coil conformation. Constrained by the disulfide bond, its backbone defines an overhand knot with frayed ends.